Peranan Statistika di Era Transformasi Digital untuk Agen Perubahan di SMAN 1 Gunungsari Lombok Barat - Purnamasari, Nur Asmita; Mustika Hadijati; Lilik Hidayati; Desy Komalasari; Zulhan Widya Baskara; Lisa Harsyiah; Jihadil Qudsi; Helmina Andriani; Dina Eka Putri; Fara Fid; Zulhan Widya Baskara (Universitas Mataram, 2025)
The digital transformation era and technological advancements demand rapid adaptability from human resources, including the increasingly important utilization of data science across various industries. Statistics, as a core component of data science, plays a crucial role in transforming data into valuable information for decision-making. Considering the significance of statistical analysis, this skill has become one of the most sought-after in today's industrial world, especially for the younger generation, such as high school students, who will become agents of change in the future. Community service activities at SMA Negeri 1 Gunungsari, Lombok Barat, aim to enhance students understanding of the role of statistics in the digital transformation era. These activities include raising awareness about the importance of statistics in career choices and the application of statistical tools in digital contexts. Furthermore, the material delivered also covers how statistics can be used as a tool to address future industrial challenges. The evaluation of this activity shows an increase in students understanding, as evidenced by the post-test results, which show significant improvement compared to the pre-test. This demonstrates that raising awareness about statistics is effective in equipping students with relevant skills in the digital era. Therefore, similar activities are expected to be implemented in other schools to strengthen students readiness to utilize statistics as agents of change in the digital transformation era.